Two dimensional graphene oxides converted to three dimensional P, N, F and B, N, F tri-doped graphene by ionic liquid for efficient catalytic performance. (October 2019) - Murugesan, Balaji; Pandiyan, Nithya; Arumugam, Mayakrishnan; Veerasingam, Muthulakshmi; Sonamuthu, Jegatheeswaran; Jeyaraman, Anandha Raj; Samayanan, Selvam; Mahalingam, Sundrarajan
Abstract: Over the past few decades, three-dimensional graphene-based materials have attracted the interest of researchers, and the investigation of their potential applications in sensors, catalysis, energy storage and electronic devices due to their extraordinary physicochemical properties has rapidly progressed. This work is focused on the preparation of 3D graphitic carbon networks co-doped by N, F, P or B by self-assembling ionic liquids such as BMIM-PF6 and BMIM-BF4 . The enhanced properties of the 3D PNF-rGO and BNF-rGO was proved by XRD, FTIR, RAMAN, and XPS spectroscopy. Most interestingly we observed that both the material displays 3D morphology (nanosphere and cubes) in FE-SEM and HR-TEM analysis. Furthermore, the synthesized material exhibited the excellent catalytic activity in OER with an overpotential of 110 and 170  mV at a current density of 236 and 176 mA/cm 2 with prolonged stability over 12 h. These results further confirmed by Tafel slope and EIS measurements. The smaller Tafel slope 73, 90 mV/dec and lower resistance 18Ω, 37Ω were obtained for PNF-rGO and BNF-rGO respectively. In addition, this catalyst showed exceptional catalytic activity toward the reduction of 4-NP. The PNF-rGO and BNF-rGO reduce the 4-NP within 1.83 and 2.33 min. The observed rate constant and TOF values are better than those of the previously reported graphene-based nonmetallic catalysts. Graphical abstract: Image 1